On the transactions costs of UK quantitative easing - Francis J. Breedon (Queen Mary University of London, School of Economics and Finance, 2018)
Most quantitative easing programmes primarily involve central banks acquiring government liabilities in return for central bank reserves. In all cases this process is undertaken by purchasing these liabilities from private sector intermediaries rather than directly from the government. This paper estimates the cost of this round-trip transaction - government issuance of liabilities and central bank purchases of those liabilities in the secondary market - for the UK. I estimate that this cost amounts to about 0.5% of the total value of QE (over 1.8 billion in my sample). I also find some evidence that this figure is inflated by the unusual design of UK QE operations.
Keywords: G12; E58; 330; Quantitative Easing; Auctions; Government Bonds